Mengoptimalisasi Kegiatan Pengembangan Diri Tari di SMAN 1 Matur - Femyla Maharani Walfis; Yuliasma Yuliasma (Jurnal Mahasiswa Kreatif, 2023)
. This study aims to know and describe how to Optimize Dance Self-Development Activities at SMAN 1 Matur. The type of research used is qualitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments in the form of stationery and cameras. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are identifying data, clarifying data, describing data, analyzing data and inferring data. The results showed that efforts that can optimize self-development activities at SMAN 1 Matur are by increasing the schedule of activities, readiness of limbs, selection of material, using learning methods, correcting student movements in each meeting and evaluation. The optimization efforts carried out make dance self-development activities interesting so that students are encouraged and enthusiastic to take part in dance self-development activities. The efforts made are very suitable to be applied to dance self-development at SMAN 1 Matur because after researchers apply these efforts, students who take part in dance self-development activities get good performances and overall students are able to perform salsa dance well and beautifully.